Intrathoracic Fibrodysplasia Ossificans Progressiva - Özkan, Serdar; Alp, Ebru; Demirağ, Funda; Yazıcı, Ülkü; Karaoğlanoğlu, Nurettin (The Thoracic and Cardiovascular Surgeon, 2014)
Fibrodysplasia ossificans progressiva is an extremely rare disease that is usually seen in the form of sporadic cases and seems to be localized outside of the thoracic cavity. Inflammation and trauma are accused in the etiology, and too many diagnostic mistakes are done. The disease, which may present genetic transmission and has not a definitive treatment, was seen as an intrathoracic mass for the first time. Intrathoracic mass was excised, and the cure was achieved in our patient, who was defined to be sporadic as a result of familial screening.
Keywords: fibrodysplasia ossificans progressiva; heterotopic ossification; intrathoracic